THE IMPACT OF ELECTRONIC PUBLISHING ON THE COMMUNICATION OF SCIENCE - Meadows, A.J. (Malaysian Journal of Library and Information Science, 1997)
Scientists have always been major users of computers and networks as part of their research involvement. Hardly surprisingly, they have therefore also pioneered the use of information technology as a communication channel. A shift from print to electronic communication in science is currently under way. The question examined here is how this will affect scientists (as both authors and readers) along with publishers and librarians. Electronic journals are used as a case study, since their numbers are beginning to grow rapidly. It is concluded that an extended transition period from printed to electronic sources can be expected, which will make information handling more complex for all participants (though perhaps especially for librarians).